FOREX TRADING AS A PART TIME EARNING OPPORTUNITY AND AS A METHOD OF EARNING FOREIGN CURRENCY - A PRIMARY STUDY DONE IN SRI LANKAN CONTEXT - Karannagoda, Neluka Maduranga (My University, 2016)
The word “Forex” which troubles us to understand stands for Foreign Currency Market. Many people know about Foreign Currency Market, but they do not know about Forex as it is an unfamiliar word for them. However, as it is mentioned, Foreign Currency Market is a place where Foreign Currencies are exchanged. In Forex,foreign currencies are exchanged between buyers and sellers and ultimately it determines the value of a certain currency in the market. Actually, Forex is the largest exchange market in the world. Also this is the only place that any person can join and earn without any conditions. Therefore it is possible to say that this is a large job market. There are no limits to the available job opportunities in Forex. Also it is opened 24 hours per day and anyone can join it through internet at any place using the computer or Android devise.Therefor if someone can join the Forex and behave in a profitable way he can earn an extra income as well as foreign currency for his country. But the problem is, in Sri Lanka forex trading is not legally authorized.As the foreign currency account of Sri Lanka is a closed one it is not allowed to invest in foreign currency market for the general public.
Keywords: Forex Trading, Self-Employment, Sri Lanka